2019
DOI: 10.1002/kjm2.12102
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA GAS5 silencing inhibits the expression of KCNQ3 by sponging miR‐135a‐5p to prevent the progression of epilepsy

Abstract: Epilepsy is one of the most common neurological disorders in humans. Recently, long noncoding RNAs (lncRNAs) have been reported to be important players in neurological diseases. Herein, this study aimed to examine the effect of lncRNA GAS5 on the occurrence of epilepsy in rat and cell models of epileptic seizure. The expression of lncRNA GAS5 was measured in the established rat and cell models. The binding sites between lncRNA GAS5 and miR‐135a‐5p, as well as those between miR‐135a‐5p and 3′ untranslated regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 37 publications
3
10
0
Order By: Relevance
“…For instance, GAS5 was upregulated in atherosclerosis, suggesting that GAS5 implicated in the development of atherosclerosis [22]. Moreover, the expression levels of GAS5 remarkably increased in epilepsy and ischemic heart disease [23,24]. Additionally, in this study, we found that GAS5 expression signi cantly downregulated in osteosarcoma, which was also consistent with some reports.…”
Section: Discussionsupporting
confidence: 92%
“…For instance, GAS5 was upregulated in atherosclerosis, suggesting that GAS5 implicated in the development of atherosclerosis [22]. Moreover, the expression levels of GAS5 remarkably increased in epilepsy and ischemic heart disease [23,24]. Additionally, in this study, we found that GAS5 expression signi cantly downregulated in osteosarcoma, which was also consistent with some reports.…”
Section: Discussionsupporting
confidence: 92%
“…was a co-occurrence and characteristic phenotype in different epilepsy models, which suggested that miR-135a-5p might serve as a potential biomarker of epilepsy. In addition, previous studies demonstrated that miR-135a-5p inhibition effectively alleviated epilepsy-induced nerve injury (20,33). In the present study, the number of BV2 cells was significantly increased and the rate of apoptosis was notably decreased by miR-135a-5p inhibitor transfection, which suggested that miR-135a-5p might serve as a potential therapeutic target for epilepsy.…”
Section: Discussionsupporting
confidence: 71%
“…Moreover, SIRT1 inhibition attenuated, but did not completely block the effects mediated by miR-135a-5p inhibitor. There are a number of potential explanations for the aforementioned findings: i) There was a high level of SIRT1 protein expression following siRNA transfection, and the residual SIRT1 protein might be sufficient to regulate cell survival; ii) miR-135a-5p might serve roles via other target proteins, for example, it has been reported that potassium voltage-gated channel subfamily Q member 3, caspase activity and apoptosis inhibitor 1 (CAAP1) and other proteins are regulated by miR-135a-5p, and participate in cell proliferation and apoptosis (20,33); and iii) as aforementioned, SIRT1 protein expression levels and activity levels were dynamically altered post-seizure, thus inhibiting SIRT1 protein expression might trigger other cellular mechanisms, resulting in a compensatory effect.…”
Section: Discussionmentioning
confidence: 99%
“…As one of the most prevailing neurological syndromes, epilepsy influences over 50 million individuals globally [1]. The principal feature linked with epilepsy is intense and frequent aberrant emission of brain neurons, clinically manifested with dysfunction of transient central nervous system (CNS) [2].…”
Section: Introductionmentioning
confidence: 99%
“…Contemporary studies have determined that specific lncRNAs are closely linked with epilepsy. For instance, evidence provided by Li et al emphasizes that lncRNA GAS5 silencing obstructed the onset and progression of epilepsy [2].…”
Section: Introductionmentioning
confidence: 99%